Purging of impure income: a comparative study of the existing purging methodologies - Wasiullah Shaik Mohammed; Mufti Abdul Kader Barkatulla; Mohammed Husain Khatkhatay; Zaffar Abbas (ISRA International Journal of Islamic Finance, 2017)
Purpose: The purpose of this paper is to study the concept of purging and present a comparative study of the existing purging methodologies prevailing in the market with a view to evolving a more effective method of capturing the entire impure income to be purged. Design/methodology/approach: To illustrate the present discussion, a case study of purging based on numerical examples has been included. The argument has also been supported with empirical data related to the universe of Sharīʿah-compliant stocks listed on Indian stock exchanges. Findings: During the study, it was found that the existing purging methodologies of calculating impure income to be purged have conceptual and practical shortcomings. Research implications/limitations: The scope of the current research is limited to calculation of impure income which accrues on account of Sharīʿah non-compliant investments directly or indirectly. It does not try to quantify the benefit which may be imputed in the form of capital gains made in trading of the investee company shares due to higher market value of the shares as a result of the impure income earned by the investee company. The paper has focused on identifying and calculating the impure income on account of interest. Impure income earned from specific Sharīʿah non-compliant products or services has not been considered directly. The reason for this is that companies dealing in such products or services are generally excluded at the business screening stage itself. In the case of those companies which derive a relatively small proportion of their total income from such activities and pass the business screening stage, the quantum of the impure income is not generally reported separately in company accounts. Practical implications/limitation: The result of adopting the proposed methodology will lead to complete purging of impure income (to the extent that is possible under present Company Law and stock exchange reporting regulations). Implementation of the proposed method requires a proper understanding of the working of listed companies and either a sound mathematical background or access to a software application to calculate the impure income to be purged. Originality/value: The current paper is original and based on the authors' personal understanding and experience of providing Sharīʿah consultancy services related to Sharīʿah-compliant investments.
Keywords: 330; India; AAOIFI; Dow Jones; Indian capital market; Purging; Impure income; Sharīʿah-compliant investment; TASIS